Evaluating the Role of Mechanical Connections and Reinforcements in Modular Timber Beam Behaviour - Mamat, Mohd Rizuwan; Mohd Hashim, Mohd Hisbany; Md Nor, Noorsuhada (Journal of the Civil Engineering Forum, 2026)
Modular timber construction faces critical challenges in connection performance, with mechanical joints representing the weakest structural elements in segmented systems, particularly for rapid-deployment infrastructure applications such as temporary forest bridges. This research addresses the fundamental knowledge gap regarding the combined effects of mechanical connections and reinforcement strategies on modular timber beam structural behavior. The study investigates modular timber beam flexural performance through experimental evaluation of steel U-shaped connectors and Chopped Strand Mat (CSM) reinforcement applied to the tension zones, examining how beam segmentation affects structural integrity. Ten I-section modular timber beams with lattice-web configuration underwent three-point bending tests using a Shimadzu AG-IS 100 kN Universal Testing Machine at 6.6 mm/min loading rate, with specimens spanning 3.0 meters supported at 2.7-meter intervals. Test specimens featured varying segmentation patterns (0.6m, 0.75m, 1.0m, and 1.5m segment lengths) connected via U-shaped steel connectors and bolts, with selected beams receiving 5mm thick CSM reinforcement at the bottom flanges. Mechanical properties including modulus of elasticity (MOE), modulus of rupture (MOR), and flexural stiffness were systematically measured to quantify reinforcement and segmentation effects on joint behavior and structural continuity. Results demonstrate that CSM reinforcement provides substantial performance improvements, with ETR136 achieving a 49% increase in ultimate load capacity (29,397 N vs 19,709 N for ETN131) and superior ductility characteristics. However, segmentation introduces significant structural vulnerabilities, with five-segment beams (ETN50.65) showing a 49.5% capacity reduction compared to continuous specimens. The research reveals that while CSM reinforcement effectively delays crack initiation and reduces peak tensile strain by an average of 31%, mechanical joints remain critical failure points due to stress concentrations at the timber-bolt interfaces. The three-segment configuration emerges as optimal for balancing structural performance with practical modularity requirements. These findings provide essential design guidance for modular timber systems in rapid-deployment applications, emphasizing the need for optimized connection strategies and hybrid reinforcement techniques to enhance the structural integrity and durability of segmented timber infrastructure.